Determinants of Technical Efficiency in Smallholder Corn Crop Farming: Application of Stochastic Frontier Production Function - Edison, Edison (International Journal of Science, Technology & Management, 2021)
Agricultural expansion such as corn expansion is often associated with extensification and resulting land acreage loss. Best input practices could increase production and yields and thus potentially reduce land expansion. This study aims to investigate the ability of input, such as land and other factors to affect production in terms of technical efficiency, and investigate the best input practices on corn technical efficiency. Primary and secondary data are used to answer the research objectives. In this study, corn data were used in the 2019 Planting Season. A sample of 120 farmers was taken randomly by applying stratified random sampling that based on land area. Appropriate qualitative and quantitative data analysis methods are used which are distinguished based on their research objectives using the empirical model of production functions, and the technical efficiency model. The results show that all input has an effect to increase corn yield, and support technical efficiency increasing the effect of input using. However, the effect of input using on yields appears to operate through other methods but technical efficiency increases.